MSMEs Move Up a Class: Sustainable Strategies to Encourage MSMEs to Enter the International Market - Fitri, Raisa; Mala, Iva Khoiril; Setiawan, Bagus; , Sudarmiatin (International Journal of Business, Economics, and Social Development, 2024)
Blitar City is the largest producer of jimbe drums in East Java, and even in Indonesia. The market segment for jimbe drum products is China and Canada. However, not all jimbe drum craftsmen in Blitar City are able to access the export market. This study aims to (a) Identify the characteristics of SMEs in the Jimbe drum industry in Blitar City (b) Describe the obstacles faced by jimbe drum craftsmen to move up to the export market (c) Develop strategies to encourage SMEs in the jimbe drum industry in Blitar City to move up in a sustainable manner. The type of research is a qualitative case study. The subjects of the study were jimbe drum craftsmen in Sentul Village, Blitar City, Head of the Cooperatives and MSMEs Office of Blitar City, Head of the Trade and Industry Office, Head of Sentul Village, Blitar City. Data collection was carried out by direct interviews with research subjects, observation and documentation. Triangulation of methods and data sources was carried out to obtain accurate data. Data analysis using the Miles, Huberman and Saldana (2024) formula and SWOT analysis. The results of the study showed that there are 2 types of Jimbe drums MSMEs in Sentul village, namely craftsmen and collectors, who do not yet have an association/ cooperative to accommodate the aspirations of craftsmen. The obstacles faced revolve around the difficulty of accessing capital and obtaining raw materials. Based on the SWOT analysis, the appropriate strategy for sustainable upgrading is to first improve the organization, help access capital and increase international marketing reach through partnerships.